EFFECT OF ALOE VERA IN LOWERING BLOOD GLUCOSE LEVELS ON DIABETES MELITUS - Aveonita, Rr. Agatha Rhana (Majority, 2015)
Abstract Diabetes mellitus (DM) is an illness or a chronic metabolic disorder with multiple etiology that is characterized by high blood sugar levels with impaired metabolism of carbohydrates, lipids and proteins as a result of insulin insufficiency. There are four pillars of therapy for diabetes patients: nutrition therapy, pharmacological, physical exercise, and education. Diet is an effective way to lower blood glucose levels. By reducing foods that contain high levels of sugar and consuming foods that can lower blood sugar levels, the levels of blood glucose will be controlled. One of the foods that can lower blood glucose levels is aloe vera. Aloe vera has potent hypoglycemic, such as: chromium and antrhaquinon. Keyword: Aloe vera,antrhaquinon, blood glucose, chromium, diabetes melitus Abstrak Diabetes Melitus (DM) didefinisikan sebagai suatu penyakit atau gangguan metabolisme kronis dengan multi etiologi yang ditandai dengan tingginya kadar gula darah disertai dengan gangguan metabolisme karbohidrat, lipid dan protein sebagai akibat dari insufisiensi fungsi insulin. Terdapat 4 pilar penatalaksanaan DM yaitu terapi gizi, farmakologi, latihan jasmani, dan edukasi. Pengaturan diet merupakan cara efektif untuk menurunkan kadar glukosa darah. Dengan mengurangi makanan yang mengandung kadar gula tinggi serta mengkonsumsi makanan yang dapat menurunkan kadar gula darah maka kadar glukosa darah akan terkontrol. Salah satu bahan pangan yang mampu menurunkan kadar glukosa darah adalah lidah buaya. Lidah buaya memiliki kandungan kimia yang berkhasiat hipoglikemik, seperti contohnya: kromium dan antrakuinon. Kata kunci : antrakuinon. diabetes melitus, glukosa darah, kromium, lidah buaya